2021
DOI: 10.1007/s42448-021-00078-6
|View full text |Cite
|
Sign up to set email alerts
|

In the Best Interest of the Child: the Norwegian Approach to Child Protection

Abstract: In the present paper, we discuss three challenges with the Norwegian Child Protective System (CPS) that might have contributed to the recent criticism from the European Court of Human Rights (ECtHR). First, how to balance the rights of the child with those of the parents. Second, the psychological field’s influence on the interpretation of what constitutes the best interest of the child, and third we describe several missing links in the CPS work. Throughout the paper, we find indications of a well-developed A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This understanding of children underlies Norwegian child welfare practices, where children are placed at the centre of the work (Melinder et al, 2021). This was further reflected in how the practitioners talked about (the inclusion of) children and their rights to participate.…”
Section: Resultsmentioning
confidence: 99%
“…This understanding of children underlies Norwegian child welfare practices, where children are placed at the centre of the work (Melinder et al, 2021). This was further reflected in how the practitioners talked about (the inclusion of) children and their rights to participate.…”
Section: Resultsmentioning
confidence: 99%
“…Promoting and protecting children's (and women's) rights are essential parts of the Norwegian self-image and international reputation, which was recently harmed by international criticism of, and court rulings about, the extensive use of forced removals by the Child Welfare System (CWS). Several rulings by the European Court of Human Rights found that Norway has paid little attention to the parents' right to family life, insisting that the child's best interests should be explicitly balanced against the rights of the parents and that the CWS tends to prevent family reunification (Melinder et al 2021). Child protection is also of concern to the UN Committee on the Rights of the Child (2018), questioning Norway's use of forced removals as in the children's best interests, insufficient communication with ethnic minority families, and cultural and language disruptions for children with ethnic minority backgrounds in state custody.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of such experts in care proceedings is debated. Areas of debate include how much the expert evidence should be weighted in court, which qualifications the experts should have (Bala et al, 2017; Melinder et al, 2021; Richman, 2005) and how the expert may best inform the court (Bogacki & Weiss, 2007; Stevenson, 2012; Tillyard QC, 2012). In reviewing the literature (Greve et al, 2023), we find little knowledge of the use of independent experts from the social workers' perspective, as much of the literature focuses on either the expert (e.g., Blacker et al, 2016; Connell, 2008) or the court (e.g., Bainham, 2009; Erickson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%